One Size Does Not Fit All: Developing Common Standards for Outcomes in Early-Phase Clinical Trials of Sound-, Psychology-, and Pharmacology-Based Interventions for Chronic Subjective Tinnitus in Adults - Hall, DA (2019)
Good practice in clinical trials advocates common standards for assessing and reporting condition-specific complaints ("outcome domains"). For tinnitus, there is no common standard. The Core Outcome Measures in Tinnitus International Delphi (COMiT'ID) study created recommendations that are relevant to the most common intervention approaches for chronic subjective tinnitus in adults using consensus methods. Here, the objectives were to examine why it is important to tailor outcome domain selection to the tinnitus intervention that is being evaluated in the clinical trial and to demonstrate that the COMiT'ID recommendations are robust. The COMiT'ID study used an online three-round Delphi method with three separate surveys for sound-, psychology-, and pharmacology-based interventions. Survey data were analyzed to assess quality and confidence in the consensus achieved across surveys and stakeholder groups and between survey rounds. Results found participants were highly discriminatory in their decision-making. Of the 34 outcome domains reaching the prespecified consensus definition in the final round, 17 (50%) were unique to one intervention, while only 12 (35%) were common to all three. Robustness was demonstrated by an acceptable level of agreement across and within stakeholder groups, across survey rounds, across medical specialties (for the health-care practitioners), and across health-care users with varying tinnitus duration. There were few dissenting voices, and results showed no attrition bias. In conclusion, there is compelling evidence that one set of outcomes does not fit all therapeutic aims. Our analyses evidence robust decisions by the electronic Delphi process, leading to recommendations for three unique intervention-specific outcome domain sets. This provides an important starting point for standardization.